Manihot esculenta leaf as to conventional anti-coccidial in Gallus gallus domesticus - Kamaruzzaman, Muhammad Hafiz (2017)
A study was conducted to evaluate the number of oocytes which is oocytes per gram (OPG) in village chicken and effect on weekly body weight of the village chicken. In general, coccidiosis is one of the most common intestinal parasite that reduce the productivity of chickens, especially when are reared under traditional system. In general, this project is to determine the effectiveness of dietary cassava leaf supplementation to control coccidiosis in village chicken and to determine the effectiveness of dietary cassava leaf in reducing oocytes count in the chicken gut and its effect on growth performance of village chicken. The total number of the chicken were used to calculate the number of oocytes and body weight of the chicken were 27 chickens. Location of this study was at Unit Poltri, Ladang 2 Universiti Putra Malaysia. Fecal analysis was conducted at Parasite Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia. This study was carried out from August until September 2016. Proximate analysis was conducted at Nutritional laboratory, Department of Animal Science, Faculty of Agriculture, Universiti Putra Malaysia. The experiment unit for this project was the UPM village chicken (Gallus gallus domesticus), cassava leaves and coccidiostat. There were 3 treatments, each with 3 replicates, and 3 chickens per replicate. The first treatment was a chicken grower diet (control diet), the second treatment was control diet + cassava leaf at 3% level and the third treatment was control diet + 1% coccidiostat. The experimental design was a Complete Randomized Design. Village chickens, aged 8 weeks from a free-range area was transferred to broiler cages according to treatment groups. Cassava leaves was collected, dried in the oven for 48 hours at 60ºC and then ground and mixed the grower feed. Dietary cassava leaf and coccidiostat were given at day 1 to day 4 only. The parameters recorded in this experiment were the number of coccidia oocytes per gram (OPG) of faeces (weekly basis) and weekly bodyweight of chicken. A one-way analysis of variance (ANOVA) by using Duncan Multiple Range Test was done for the experimental data. The number of coccidia oocytes in treatment 1 was significantly higher oocytes counts than treatments 2 and treatment 3. However, Treatment 2 and treatment 3 were not significant (P<0.05), so it indicated positive effect of dietary cassava leaves and coccidiostat in prevention of coccidiosis, with levels of oocytes falling below 300 OPG, indicate infection level. For the weekly bodyweight shown there was no significant difference in weekly bodyweight among village chicken in all treatments (P<0.05). The bodyweight among village chicken increase disregard the presence or absence of anti-coccidial supplements. Throughout for this study, it shown that cassava leaves have anticoccidial effect and can be used to replace coccidiostat in chicken production.